Uncovering miRNA regulatory mechanisms through functional assessment of miRNA-centered complexes during C. elegans development - Hebbar, Shilpa (Kansas State University, 2022)
Normal developmental and physiological processes depend on precise regulation of gene expression. miRNAs are a class of small non-coding RNAs that post-transcriptionally regulate gene expression by inducing gene silencing through translational inhibition and mRNA target destabilization. Currently, there is a lack of understanding of how miRNA biogenesis and activity is regulated under different developmental contexts or how they integrate with other regulatory signals. Using C. elegans as a model, we sought to address this gap in our knowledge by identifying components of miRNA-centered complexes and characterizing the molecular mechanisms through which they interact with miRNAs to regulate gene expression. miRNA pulldowns followed by mass spectrometric analysis of precipitated complexes identified 211 protein interactors of let-7, miR-58, and miR-2 miRNAs. To determine which of these interactors are functionally important for miRNA activity, we performed an RNAi screen of genes encoding a subset of miRNA complex components. Depletion of 26 of the 40 tested genes modified the miRNA mutant phenotypes in one or more functional assays, suggesting they play a role in miRNA-mediated gene regulation. Among the miRNA interactors found to be functionally important for miRNA activity were RNA binding proteins, splicing, and translational regulators suggesting a potential interplay between gene regulatory processes. We sought to further characterize one candidate identified through our functional proteomics approach, HRPA-1. hrpa-1 depletion enhanced developmental phenotypes of miRNA mutants, disrupted miRNA levels, and affected global gene expression profiles, consistent with an HRPA-1 role in gene expression regulation. Among the genes differentially expressed in hrpa-1 depleted animals was R06C1.4, a homolog of yeast cleavage and polyadenylation factor complex (CFI) component. Depletion of R06C1.4 partially recapitulated the enhancement effects on miRNA mutant developmental phenotypes observed with hrpa-1 loss. Thus, we identified a potential role for R06C1.4 in mediating developmental gene expression downstream of hrpa-1. We propose several models describing potential mechanisms through which HRPA-1 may coordinate with miRNAs to regulate gene expression. Overall, this work identified novel factors that functionally support miRNA gene regulatory activity, discovering possible modes through which one such factor (HRPA-1) coordinates with miRNAs. In addition, this work generated avenues for future mechanistic investigations aimed at characterizing the dynamic nature of post-transcriptional gene regulation.
Keywords: MicroRNAs; C. elegans; Gene regulation; RNA binding proteins